Miniaturisasi Antena Mikrostrip Pencatu Ganda Menggunakan Metode Peripheral Slit - Syah Alam; Lydia Sari; Indra Surjati; Newton Onasie (Jurnal Rekayasa Elektrika, 2021)
This research proposes a dual-feed microstrip antenna using a peripheral slit for mobile communication systems. Miniaturization and reduction of the dual feed microstrip antenna’s size have been investigated and explained in this paper. The proposed antenna dimensions are reduced using three pairs of slits while the resonant frequency is 1800 MHz. Based on simulation and optimization results, the proposed antenna dimensions can be reduced by 94.81% compared to conventional multiple feed channel microstrip antennas. These results indicate that the peripheral slits technique has succeeded in reducing the proposed antenna dimensions without changing its frequency. We get a reflection coefficient of -31.65 dB, VSWR of 1,053 at a frequency of 1.95 GHz, and bandwidth of 206 MHz with a frequency range from the measurement process of 1.85 GHz–2.06 GHz with a bandwidth of 210 MHz. Impedance obtained from the proposed antenna is 47.72 ± j0.67 Ω at frequency 1.95 GHz.